2019
DOI: 10.1039/c9nr06509a
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and up-conversion properties of full spectrum CsPbX3 (X = Cl, Br, I) quantum dot glasses

Abstract: Multi-color up-conversion emission of CsPbX3 (X = Cl, Br, I) quantum dot glasses under two-photon excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The PL peak at ≈506 nm may come from the BE carrier recombination of the α‐Er/Yb:CsPb(Cl/Br) 3 , since the free excitons are usually unstable at room‐temperature due to small exciton binding energy in 3D perovskite. [ 30,31 ] The bandgap of the α‐Er/Yb:CsPb(Cl/Br) 3 can be estimated by the photon energy of its PL peak, 2.45 eV. At the same time, using the Cl:Br ratio (1:2) determined from EDX characterization, the bandgap of the α‐Er/Yb:CsPb(Cl/Br) 3 can be estimated to be 2.45 eV, which is consistent with the photon energy of the PL peak at 506 nm (see Table S2, Supporting Information).…”
Section: Resultssupporting
confidence: 66%
“…The PL peak at ≈506 nm may come from the BE carrier recombination of the α‐Er/Yb:CsPb(Cl/Br) 3 , since the free excitons are usually unstable at room‐temperature due to small exciton binding energy in 3D perovskite. [ 30,31 ] The bandgap of the α‐Er/Yb:CsPb(Cl/Br) 3 can be estimated by the photon energy of its PL peak, 2.45 eV. At the same time, using the Cl:Br ratio (1:2) determined from EDX characterization, the bandgap of the α‐Er/Yb:CsPb(Cl/Br) 3 can be estimated to be 2.45 eV, which is consistent with the photon energy of the PL peak at 506 nm (see Table S2, Supporting Information).…”
Section: Resultssupporting
confidence: 66%
“…[ 42,43 ] These CsPbX 3 NCs embedded glasses have shown great potential towards various applications such as LEDs, [ 39 ] cryogenic temperature sensors, [ 42 ] data storage, [ 44 ] and low‐threshold lasers. [ 45,46 ] In this work, CsPbX 3 NCs were embedded into glasses and femtosecond transient absorption (fs‐TA) spectroscopy was utilized to investigate the ultrafast ASPL process. The results revealed that FEs were formed with the assistance of phonons under SGE, and within a few ps, these FE thermally dissociated into free carriers, which led to the ASPL through the radiative recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite QD particle size increases with the increase in heat treatment temperature, and the size of the QDs in the glass affects exciton binding energies. 37,38 As the exciton binding energy exceeded 100 meV, the electron−hole pair became tightly bound such that it would be unlikely to diffuse with lattice vibration. 13 We assumed the excitons to be tightly bound Frenkel excitons rather than Wannier Mott excitons coupled with lattice vibrations 13,19 Based on the above results, the unique PL properties of 0-D Cs 4 PbBr 6 QDs in glass were unaffected by the coexistence of 3-D CsPbBr 3 ; therefore, we examined other plausible explanations for the PL behavior of bulk Cs 4 PbBr 6 QD glass.…”
Section: ■ Results and Discussionmentioning
confidence: 99%